More than a snapshot in time: Pathways of disadvantage over childhood - Mensah, Fiona K; Azpitarte, Francisco; Chong, Shiau; Goldfeld, Sharon; Badland, Hannah; Redmond, Gerry; Williams, Katrina; O'Connor, Elodie; Woolfenden, Sue; O'Connor, Meredith; Cloney, Dan (My University, 2018)
Background: Disadvantage rarely manifests as a single event, but rather is the enduring context in which a child’s development unfolds. We aimed to characterize patterns of stability and change in multiple aspects of disadvantage over the childhood period, in order to inform more precise and nuanced policy development. Methods: Participants were from the Longitudinal Study of Australian Children birth cohort (n¼ 5107). Four lenses of disadvantage (sociodemographic, geographic environment,health conditions and risk factors), and a composite of these representing average exposure across all lenses, were assessed longitudinally from 0 to 9 years of age. Trajectory models identified groups of children with similar patterns of disadvantage over time for each of these lenses and for composite disadvantage. Concurrent validity of these trajectory groups was examined through associations with academic performance at 10–11 years. Results: We found four distinct trajectories of children’s exposure to composite disadvantage, which showed high levels of stability over time. In regard to the individual lenses of disadvantage, three exhibited notable change over time (the sociodemographic lens was the exception). Over a third of children (36.3%) were exposed to the ‘most disadvantaged’ trajectory in at least one lens. Trajectories of disadvantage were associated with academic performance, providing evidence of concurrent validity. Conclusions: Children’s overall level of composite disadvantage was stable over time, whereas geographic environments, health conditions and risk factors changed over time for some children. Measuring disadvantage as uni-dimensional, at a single time point, is likely to understate the true extent and persistence of disadvantage.
International Journal of Epidemiology
Keywords: Children; Health; Health and wellbeing; Health; Children; Health and wellbeing